ENERGI LISTRIK DAN PEMBANGUNAN MANUSIA: BUKTI EMPIRIS DARI TINGKAT PROVINSI DI INDONESIA - Ivana Suprapto; Uswatun Hasanah (Syiah Kuala University, 2022)
Abstract This study aims to analyze the effect of the electrification ratio on HDI in Indonesia for general and specific purpose: with a specific analysis of provinces divided into various categories. The slow growth rate of HDI and the disparity of HDI in various provinces has pushed the government to work out the right solution to overcome these problems. One effort that can be done is to encourage an equal electrification ratio between provinces. The electrification ratio is known to have an important role in improving all indicators in HDI, which include economy, health and education. This study uses panel data from 33 provinces in the year 2010-2018, with the fixed effect estimation method. The other variables used in this study consist of density population, the number of poor in the population, the number of health and education facilities, and the number of teachers and health workers. The empirical results show that in general the electrification ratio has a positive effect on HDI. Meanwhile, the effect of the electrification ratio in various categories of provinces shows that the results can be positive or negative. The electrification ratio has the greatest effect on the sub-categories of provinces that have low GRDP, low HDI and low IPM low GRDP performance